2019
DOI: 10.1101/713180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal integration of narrative information in a hippocampal amnesic patient

Abstract: Default network regions appear to integrate information over time windows of 30 seconds or more during narrative listening. Does this long-timescale capability require the hippocampus? Amnesic behavior suggests that the hippocampus may not be needed for online processing when input is continuous and semantically rich: amnesics can participate in conversations and tell stories spanning minutes, and when tested immediately on recently heard prose their performance is relatively preserved. We hypothesized that de… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 42 publications
(86 reference statements)
4
12
0
Order By: Relevance
“…We find that, if the model is allowed to continuously maintain information in working memory (i.e., there are no distractions/interruptions that clear out the working memory state), the model is sensitive to stimulus history, even if the hippocampus is completely inactivated. This result fits with the results of a recent patient study (Zuo et al, 2020) that showed that an amnesic patient’s brain response was sensitive to “scrambling” which parts of a movie preceded the current part, as well as other, more anecdotal results showing that hippocampal patients can comprehend narratives so long as they are not interrupted (Milner et al, 1968).…”
Section: Brief Summaries Of Simulationssupporting
confidence: 89%
See 2 more Smart Citations
“…We find that, if the model is allowed to continuously maintain information in working memory (i.e., there are no distractions/interruptions that clear out the working memory state), the model is sensitive to stimulus history, even if the hippocampus is completely inactivated. This result fits with the results of a recent patient study (Zuo et al, 2020) that showed that an amnesic patient’s brain response was sensitive to “scrambling” which parts of a movie preceded the current part, as well as other, more anecdotal results showing that hippocampal patients can comprehend narratives so long as they are not interrupted (Milner et al, 1968).…”
Section: Brief Summaries Of Simulationssupporting
confidence: 89%
“…Inter-subject analyses are widely used in naturalistic studies, such as the studies by J. Chen et al (2016) and Zuo et al (2020) that we discuss in Simulations 1, 6, and 7 . Comparing data across subjects requires some form of alignment.…”
Section: Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In support, prior work suggests that temporal integration of narrative information during movie watching in Dorsal PMN regions may not depend on interactions with the hippocampus (Chen et al, 2016;Zuo et al, 2020). The hippocampus has been previously characterized as a gateway between the PMN and an anterior temporal (AT) network that processes item and emotional information (Ranganath & Ritchey, 2012;Ritchey, Libby, et al, 2015).…”
Section: Discussionmentioning
confidence: 78%
“…The following subjects received the “Pie Man” stimulus on two separate occasions (specified by or in the BIDS file naming convention): , , , , , , , , , , , , , . We recommend excluding subjects (both and ), (), (), , , , , , and (as specified in the file in the directory) based on criteria explained in the “Intersubject correlation” section of “Data validation.” Subsets of the “Pie Man” data have been previously reported in numerous publications (Lerner et al, 2011, 2014; Ben-Yakov et al, 2012; Regev et al, 2013; Stephens et al, 2013; Chen et al, 2015; Simony et al, 2016; Baldassano et al, 2017; Liu et al, 2017; Vodrahalli et al, 2017; Yeshurun et al, 2017a; Zuo et al, 2020), and additional datasets not shared here have been collected using the “Pie Man” auditory story stimulus (e.g. Gross et al, 2013; Blank & Fedorenko, 2017; Iotzov et al, 2017).…”
Section: Methodsmentioning
confidence: 99%